Handling Policy on Corruption Crime in Polres Tasikmalaya - Imanudin Imanudin (Jurnal Daulat Hukum, 2018)
In this study, will be discussed are: the handling of corruption in Polres Tasikmalaya, there are obstacles in the Handling of Corruption in the Polres Tasikmalaya and solutions in dealing with the constraints in the handling of Corruption in Polres Tasikmalay. The method used in this research is normative juridical approach used to determine the extent to which the principles of the law, the synchronization vertical / horizontal, and systemic law is applied, which is based on secondary data. Based on the results of this study are very large role of Police in law enforcement to eradicate corruption. But the weakness of the laws that regulate the authority of the Police in the investigation of corruption resulted in the ineffectiveness of the investigation of cases of corruption by the police. Police Investigator action in the process of investigation of corruption practiced by the investigator in Polres Tasikmalaya, there were always obstacles that result in delays / delays in the investigation of corruption. Propose the addition of Human Resources Police as one of the measures to meet the needs of a shortage of human resources, and / or exploit the existing potential according to ability and knowledge possessed, where one of her given training and education for the field duties and functions authority relating to the handling of Corruption. Provide guidance / courses / training related to IT (Information Technology), especially in connection with the handling of Corruption;Keywords: Policy; Crime; Corruption.